Diabetes Mellitus Diagnosis Expert System With Web-Based Forward Chaining - Rusdiansyah, Rusdiansyah; Setiawan, Santoso; Badrul, Mohammad (Politeknik Ganesha Medan, 2019)
Diabetes Mellitus Diagnosis Expert System with Web-Based Forward Chaining Method. An expert system is one branch of artificial intelligence technology that combines the knowledge of an expert with tracing data to solve problems that are normally carried out by an expert. The development of information technology now makes it possible to access information from anywhere and anytime. So the role of information technology is increasingly useful to be able to develop in various fields including in the health sector. One of them is the system used to diagnose diabetes mellitus. Diabetes Mellitus is one of the most common diseases in the world. The inability of the pancreas to produce insulin normally becomes one of the reasons a person has this disease. In this research, the method used is Forward Chaining which sorts all data obtained before getting the final conclusion. The final results obtained from this study is an expert system application for diagnosing diabetes with a forward chaining method, where the user answers questions based on perceived symptoms, then the results obtained in the form of disease and explanation of the disease.